Pengaruh Profitabilitas, Struktur Modal, Likuiditas, Dan Rasio Aktivitas Terhadap Nilai Perusahaan - Yudha Pratama, I Kadek Lingga; Candradewi, Made Reina (Universitas Pahlawan Tuanku Tambusai, 2024)
Firm value is a description of the company's performance that can affect investors' assessment of a company. Investors considers that firm value is an important because firm value is an indicator of how the market perceives the company. This study aims to determine the effect of profitability, capital structure, liquidity and activity ratios on firm value. The population in this study were property and real estate sector companies that recorded profits and were listed on the Indonesia Stock Exchange in the 2020-2023 period as many as 32 companies. The sample of this study was 30 companies selected using the simple random sampling method. The analysis technique used in this research is Multiple Linear Regression. The analysis results show that profitability has a insignificant effect on firm value, capital structure has a significant negative effect on firm value, liquidity has a significant negative effect on firm value, and activity ratio has a significant positive effect on firm value. The implication of this research is that it is able to provide empirical evidence and is able to provide information to companies by paying attention to factors that affect firm value.